A pilot study of a scalable training programme for coaches delivering webSTAIR - Sherry Yam; Jamie S. Kim; Annapoorna Ayyagari; Julianna Hogan; Jan A. Lindsay; Marylene Cloitre (European Journal of Psychotraumatology)
Background: Accessible, low-cost digital programmes are emerging as a means by which to address high rates of mental health problems. However, the development and assessment of scalable training programmes for effective use of digital interventions has lagged. This is particularly important, as coach-supported digital interventions provide benefits that substantially and consistently exceed those of programmes that are entirely self-guided.Objectives: This report describes the evaluation of a brief coach training programme consisting of a two-hour workshop and six 1-hour consultation sessions for delivery of webSTAIR, a 10-module transdiagnostic web-based programme for trauma-exposed populations.Method: The training was provided to 68 mental health counsellors at Veteran Health Administration Readjustment Counselling Services, who delivered the treatment to 99 veteran clients.Results: A total of 51% of the coaches completed the programme. Client outcomes were encouraging. Veterans enrolled in the programme demonstrated significant and clinically meaningful improvements in functioning (Cohen’s d = 0.88), emotion regulation (Cohen’s d = 0.97), posttraumatic stress disorder (PCL-5 Cohen’s d = 0.61; ITQ Cohen’s d = 0.60), and depression (Cohen’s d = 0.53).Conclusions: The study contributes much needed information regarding evidence for the effectiveness of ‘light-touch’ training strategies. The data support the integration and testing of brief training programmes in the implementation and dissemination of evidence-based digital interventions. Strategies for improving training completion rates among busy providers and resource-burdened clinical services need to be considered.